Electricity Consumption and Economic Growth: A Panel Data Approach for Brazil, Russia, India, China and South Africa Countries - Khobai, Hlalefang (International Journal of Energy Economics and Policy, 2018)
This paper serves to investigate the causal relationship between electricity consumption and economic growth in the BRICS countries during the period 1990–2014. Carbon dioxide emissions and urbanisation were included as additional variables to form a multivariate framework. The Kao panel co-integration and Johansen Fisher panel co-integration techniques are applied to analyse the co-integration relationship between the variables while the Vector Error Correction Model (VECM) Granger-causality test is used to estimate the causality relationship among the variables. The study's results reveal that there is a long run relationship between the variables. The research outcome further detected a unidirectional causality flowing from economic growth to electricity consumption in the long run in BRICS countries. So in the light of determination of the study, the policy implication is that a significant transformation of low carbon technologies such as renewable energy should be implemented to curb the emissions and sustain economic growth and development. Keywords: Energy consumption, Economic growth, Causality, BRICS countries JEL Classifications: D04; Q47; Q42; Q01